The short and the long of it: Stock-flow matching in the US housing market - Eric Smith; Zoe Xie; Lei Fang (Federal Reserve Bank of Atlanta, 2022)
This paper investigates the US housing market from just before the Great Recession onward (2006-19) and assesses the viability of stock-flow matching in generating the observed outcomes. The paper documents that the probability that a house sells declines sharply after listing for two weeks. Moreover, the probability and associated price of a fast sale recover from the housing slump sooner, faster, and more prominently than slower sales. The simulated stock-flow matching model can mimic not only sales, prices, listings, and time-on-market but also capture the distinctions in quick and slower trades, indicating the importance of stock-flow matching for understanding housing market dynamics.
Keywords: E30; R21; R31; 330; housing; stock-flow matching; trading dynamics; duration dependence